Study of Secretory Status of ABO Blood Groups Antigens and Rh Typing in Dried Salivary Samples of Normal Individuals - Dawlaty, Dr.Brishna; Dr. Yousuf Yadgari MD (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Background and aim: saliva is a biological fluid that not only has valuable function in oral cavity but also important in forensic medicine for determining blood group in many crime scenes. Saliva in crime scenes mostly obtained in dried form and there are studies that show secretory status of blood group antigens in dried saliva. In this study also the aim is to observe the secretory status of ABO blood group and Rh typing in dried saliva. Material and method: This cross-sectional study was conducted in Biochemistry Department of Kabul University of Medical Science. Salivary and blood samples were obtained from 400 normal subject with 42.5% female and 57.5% male who were registered in blood donation centers of Kabul. For Blood grouping agglutination method was performed by commercial antisera. Agglutination inhibition method was used for blood grouping and Rh typing in dried salivary samples. For analyzing relation of secretory status of antigens and Rh typing chi square test was performed. Results: in this study 170 (42.5%) female and 230 (57.5%) male were participated. The mean age was 37 years with ranges between 20 and 65 years. Totally 70.25% were secretors. the highest percentage of secretors were in blood group A. Percentage of Rh factor secretors (44.8%) compared to nonsecretors was significantly low . In this study relation of gender, age with secretory status of antigen A, B and Rh typing were not statistically significant. Conclusion: Most of the secretors were belonged to blood group A. Secretory status is independent of age and gender. Result of Rh typing in saliva was not significant positive.